2021
DOI: 10.1002/adfm.202109633
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Condensation on Soft Materials through Bulk Lubricant Infusion

Abstract: Soft substrates enhance droplet nucleation during water vapor condensation because their deformability inherently reduces the energetic threshold for heterogeneous nucleation relative to rigid substrates. However, this enhancement is counteracted later in the condensation cycle, when substrate viscoelastic dissipation inhibits condensate droplet shedding. Here a polydimethylsiloxane (PDMS) based organogel is designed to overcome this limitation. It is shown that merely 5% bulk lubricant infusion in PDMS reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 65 publications
(109 reference statements)
0
14
0
Order By: Relevance
“…[49][50][51] When the surface temperature falls below the dew point, water vapor in the air tends to condense into liquid droplets, which eventually freeze after the surface temperature decreases to subzero. 52 The frozen droplets connect by ice bridges, forming condensation frosts. Once the condensation frosts on superhydrophobic surfaces are not effectively inhibited, the superhydrophobicity and anti-icing properties of surfaces will be greatly degraded owing to the high affinity of frost to water.…”
Section: High-humidity Resistance and Anti-frostingmentioning
confidence: 99%
“…[49][50][51] When the surface temperature falls below the dew point, water vapor in the air tends to condense into liquid droplets, which eventually freeze after the surface temperature decreases to subzero. 52 The frozen droplets connect by ice bridges, forming condensation frosts. Once the condensation frosts on superhydrophobic surfaces are not effectively inhibited, the superhydrophobicity and anti-icing properties of surfaces will be greatly degraded owing to the high affinity of frost to water.…”
Section: High-humidity Resistance and Anti-frostingmentioning
confidence: 99%
“…Liquid infused surfaces (LIS) have been shown to enhance droplet mobility in condensation applications, by dramatically reducing contact angle hysteresis, however the gradual loss of lubricant could make the effect short lived. [31,[36][37][38][39] Polymer infused porous surfaces also offer low contact angle hysteresis and tunability, as well as being more robust than LIS, however they are complex to fabricate and may be challenging to scale up. [37] Only recently, Cha et al have shown that a less complex hydrophilic surface with low contact angle hysteresis, can determine efficient dropwise condensation.…”
Section: Introductionmentioning
confidence: 99%
“…In case of LIS, the wetted surface is liquid rather than solid. Usually, LIS consist of a structured surface that is impregnated with a lubricant. These surfaces have attracted much attention because they provide low sliding angles. Water drops start sliding down inclined LIS even at low tilt angles.…”
Section: Introductionmentioning
confidence: 99%